A Mixed-Methods Study on the Role of Culture in EFL Teaching for Kurdish Learners - Bawar Qadir (Journal of Applied Linguistics, 2026)
This study exploresses the role of culture in English as a Foreign Language (EFL) teaching for Kurdish learners in higher education. Using a mixed-methods design, data were collected from 97 students and 48 teachers across three universities in Iraqi Kurdistan through questionnaires and interviews. The analysis combined percentage-based survey findings with thematic insights from teacher perspectives. The results indicate that cultural integration has a marked effect on language learning outcomes. A large majority of students (85%) reported that exposure to cultural contexts enhanced their communicative competence, while 78% highlighted the value of learning cultural scripts such as politeness and social norms. Similarly, 72% stressed the importance of non-verbal communication, and 90% of participants agreed that culturally relevant materials increased their motivation and classroom engagement. However, the findings also reveal notable challenges: 75% of teachers lacked sufficient training in cultural pedagogy, and 70% cited limited access to authentic cultural resources. These findings suggest that language teaching cannot be separated from cultural content without risking reduced communicative effectiveness. For EFL classrooms in Kurdistan, the study highlights the need to expand teacher training, invest in authentic cultural materials, and promote experiential learning activities. By embedding culture within language instruction, educators can foster more effective, engaging, and globally relevant learning experiences for their students. Keywords : Language teaching; culture; communicative competence; intercultural awareness;language learning